Real-time energy efficiency analysis of buildings using ir imaging and computer vision - Lupoiu Teodor; Carutasiu Mihail-Bogdan; Necula Horia (E3S Web of Conferences)
Reducing consumption of energy and emissions of greenhouse gas emissions is a critical worldwide problem, with the buildings’ sector accounting for up to 44% of fossil fuel consumption. Residential buildings, in particular, have great technical potential for energy savings. Our study addresses this by creating a model for real-time energy efficiency analysis of building insulation using infrared imagery and computer vision. The model monitors and offers important insights of energy transfer by continually evaluating a building’s thermal envelope. Additionally, an experimental stand comprising of a miniature model house made from different materials and insulation types, an IR camera and a Raspberry Pi were considered. It will provide data for an AI based model, which employs a robust and already proven architecture, YOLOv8 namely, used to determine the thermal characteristics of the analysed materials and the energy performances respectively.